Performance of an anaerobic baffled filter reactor (ABFR) - aerobic attached film bioreactor (AAFR) system in semi batch or continuous mode for treating organic wastewater dissertation - Allera, Andresa S. (2008)
Combination of anaerobic and aerobic wastewater treatment processes is employed for less energy requirement and simple aeration. In this study, the anaerobic reactor combines the characteristics of an attached film process in an anerobic baffled reactor while the subsequent aerobic treatment is carried out in a fixed film type reactor.
Experiments were performed on a bench scale treatment system involving a 300-L anaerobic reactor followed by a 200-L aerobic reactor and a 100-L settling tank operated in a continuous and semi batch mode.
Sludge from a working full-scale UASB reactor used for treatment of beer production wastewater was used for the start up of the anaerobic baffled filter reactor (ABFR). Synthetic wastewater was used during the start-up starting with low COD concentrations and increasing gradually as soon as 70-80% COD removal was achieved. The aerobic attached film reactor (AAFR) was seeded with sludge coming from the aerobic tanks of the UP Wastewater Treatment Facility. It took around 3 months to reach an OLR of 1.0 kg COD/m3 day and COD removal of 88%.
After start-up, the treatment system performance was evaluated for food processing wastewater. In the continuous mode using organic loading rates (OLR) of 1.0, 3.0, and 5.0 kg COD/m3. %COD removals of 98%, 89%, and 81% for 3-day continuous runs were obtained. For the semi batch mode, COD removals obtained for 12 hoursfilling time were 97%, 70%, 77% and similar COD removals were obtained for 8-hour filing period.
In all the experimental runs, pH at the first chamber was controlled at 7.0 with sodium bicarbonate solution. The results of semi batch operation was validated on 3.5 cu. m. pilot model and 60 cu.m. commercial plant.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Purification -- Anaerobic treatment; Sewage -- Purification -- Fixed-film biological process